Sustainability Integration Halal Supply Chain of The Food Industry: A Case Study of UD. Wnd Food Jember - Hikmatul Hasanah; Devi Hardianti Rukmana (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2026)
The halal food and beverage industry in Indonesia has shown significant growth, driven by increasing consumer awareness of halal, healthy, and environmentally friendly products. This situation demands that the halal industry not only prioritize Sharia compliance but also integrate sustainability principles, encompassing environmental, social, and economic aspects, into its supply chain. This research focuses on analyzing the integration of the halal tenets with ecological ethics, logistics efficiency strategies, the application of the zero-waste supply chain concept, and identifying barriers and opportunities in implementing a sustainable halal supply chain in the food industry. The aim is to examine in depth the integration of sustainability in the halal supply chain as an effort to support business sustainability and industrial competitiveness. Through a qualitative approach with an exploratory case study type, with data collection techniques through observation, interviews, and documentation, resulting in findings that UD. WND Food Jember has integrated halal principles with environmental ethics consistently through the use of halal-certified raw materials, hygienic production processes, environmentally friendly waste management, partnership strategies to improve logistics efficiency, and the application of the zero-waste supply chain concept through efforts to minimize waste and limited utilization of production waste. The integration of sustainability in the halal supply chain that has been carried out by WND Food Jember has become an ideal model for the development of a sustainable halal food industry for the food industry in general.